2020
DOI: 10.1097/ncc.0000000000000868
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Positive Thinking of Patients With Prostate Cancer

Abstract: BackgroundResearch has explored the effectiveness of positive thinking on individuals, but only a few studies have investigated the factors that influence individual positive thinking, particularly among patients with prostate cancer.ObjectivesThe aim of this study was to understand the factors that affect positive thinking among patients with prostate cancer and the mediating role of self-efficacy.MethodsA cross-sectional design and a convenience sampling method were used to recruit patients with prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The overall mean positive thinking score of women in the current study was 68.69, which is slightly better than that of patients who are receiving hormone treatment for advanced prostate cancer (66.1) [41] or middle-aged women in the community (66.8) [20]. The reason for such a difference in positive thinking scores among the population remains unknown, and additional research is necessary to clarify this issue.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The overall mean positive thinking score of women in the current study was 68.69, which is slightly better than that of patients who are receiving hormone treatment for advanced prostate cancer (66.1) [41] or middle-aged women in the community (66.8) [20]. The reason for such a difference in positive thinking scores among the population remains unknown, and additional research is necessary to clarify this issue.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, studies of patients with prostate cancer have found that patients with greater positive thinking experience better prostate cancer-specific QOL, social/family well-being, emotional well-being, and functional well-being [30]. An individual's positive thinking is correlated with perceived social support, general selfefficacy, and satisfaction with treatment [41]. Additional research is needed to confirm the effect of positive thinking on the health-related QOL of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Experts were invited to review the content and surface validity of the scale for patients with prostate cancer. The Cronbach’s α of the overall scale was 0.94, the subscale of personal satisfaction was 0.92, and the subscale of goal pursuit was 0.66 (Chien et al, 2022 ). The reliability and validity of the PTS-Chinese, however, have yet to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…Positive psychology focuses on the positive experiences and feelings of individuals, such as well-being, satisfaction, and happiness (Seligman & Csikszentmihalyi, 2000). Studies of the general public (Jung et al, 2007), middleaged women (Kim & Hur, 2019), and patients with prostate cancer (Chien et al, 2021(Chien et al, , 2022 and other types of cancer as well as their caregivers (Hamidou et al, 2018) have shown that positive thinkers have higher well-being, happiness (Chien et al, 2021;Kim & Hur, 2019), life satisfaction (Jung, et al, 2007), mental domain healthrelated quality of life (Hamidou et al, 2018), and quality of life specific to prostate cancer (Chien et al, 2021). Positive thinking is the mediating factor that affects the Page 2 of 9 Chien and Huang Psicologia: Reflexão e Crítica (2022) 35:31 relationships between an individual's health status and economic stress and happiness (Kim & Hur, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the disease adaptation process of cancer patients, good social support can effectively enhance patients' ability to cope with the disease and adapt to the society, help improve individual self-e cacy, reduce adverse physical and psychological symptoms and thus improve patients' negative emotions. A study on positive thinking and related factors in prostate cancer patients receiving hormone therapy conducted in Taiwan showed that self-e cacy was a mediating factor affecting the relationship between treatment satisfaction, evaluation support, and positive thinking [19]. Another study showed that social support and self-e cacy could indirectly predict the psychological stress in children with malignant tumor, with self-e cacy having the greatest total effect on psychological stress in children.…”
Section: Introductionmentioning
confidence: 99%